Approaching Trust: Case Studies for Developing Global Research Infrastructures - Flanagan, Heather; Haak, Laurel L.; Paglione, Laura Dorival (Frontiers in Research Metrics and Analytics, 2021)
Trust is a core component of collaboration. Trust is a local phenomenon, and scientific research is a global collaborative, its impact multiplied through open exchange, communication and mobility of people and information. Given the diversity of participants, local policies and cultures, how can trust be established in and between research communities? You need transparent governance processes, thoughtful engagement of stakeholder groups, and open and durable information sharing to build the “stickiness” needed. In this paper we illustrate these concepts through three trust building use cases: ORCID, Global Alliance for Genomics and Health, and SeamlessAccess, platforms sharing an identity and access technical service core, painstaking community building, and transparent governance frameworks.